Job Placement, Satisfaction, Engagement: Impact on Employee Performance: Dampak Penempatan Kerja dan Kepuasan Kerja terhadap Kinerja Karyawan: Peran Mediasi Keterlibatan Karyawan - Indah Ismiyanti; Dewi Andriyani (Universitas Muhammadiyah Sidoarjo, 2022)
This quantitative research study investigates the relationship between job placement, job satisfaction, employee engagement, and employee performance at PT. Plywood Kayu Lestari in Mojokerto City. The study's sample consists of 120 male employees, and path analysis techniques are employed to analyze the data using statistical software. The primary data is collected through a questionnaire with Likert scale measurements, which are tested for validity and reliability. The findings reveal the direct influence of job placement and job satisfaction on employee performance, and further suggest that employee engagement acts as a mediator in this relationship. The implications of these results highlight the importance of enhancing job placement strategies, fostering job satisfaction, and promoting employee engagement to improve overall employee performance. Highlights: The study investigates the impact of job placement and job satisfaction on employee performance. Employee engagement is examined as a mediating variable in the relationship between job placement, job satisfaction, and employee performance. The findings emphasize the importance of enhancing job placement strategies, fostering job satisfaction, and promoting employee engagement for improved overall performance. Keywords: Job placement, Job satisfaction, Employee performance, Employee engagement, Path analysis